A contribuição do vídeo como linguagem no ensino-aprendizagem de conceitos científicos no 9º ano do ensino fundamental - Dutra, Ana Cláudia Maquiné (2013)
This presented dissertation was intended to analyze how the teaching-learning of scientific occures in Science Teaching, having as pedagogical mediation the movies language expressed in the videos that present and discuss scientific knowledge from the curriculum design proposed for the 9th year of elementary school. Even though, their approach was qualitative in the terms of hermeneutics. The first stage of the study refers to a documentary research and diagnosis from the existent literature in order to explain how a structured set of signs interacts with thinking being possible the language, that among its purposes is human communication, as well as to clarify the language as product of thinking dowry of a meaning of what is being seen and heard from the use of videos in the classroom. The second step talks about a field research in which it‟s made visits to the TV School library, located in the Secretaria do Estado e Qualidade do Ensino - SEDUC / AM in the building of the Centro de Estudos Padre Anchieta - Cepan. In particular, the videos were analysed to present, discuss and contribute to the learning of scientific concepts, according to the Course Proposal from 6th to 9th grade of elementary school of Natural Sciences and Mathematics, available in the Management of Primary Education of the previous secretary. In the third step, was selected a higher education institution that trains teachers of natural sciences to analyse the measure or proportion of the video is being used in the initial formation. Was made an investigation documentary of the course plans of teachers who teach subjects considered the base of the act of teaching. The fourth stage of the research was intend to investigate the possible contributions of didatic videos for learning scientific concepts, from the conception of the teachers about the cited resource for the following aspects: planning and assessment of the video usage in the classroom; purpose of the video usage in classroom, criteria of selection of the videos; approach and exploration of audiovisual material and possible products generated; way of obtaining the videos, notice the students' behavior before, during and after the exposure of the videos. The analyzes presented here make clear the importance of didatic video language in the school context, stressing that it makes the science teacher leads the student in two ways: reading the world, understand it, and interpret it using the function communication to alienate